Environmental impact of white shrimp culture during 2012-2013 at Bandon Bay, Surat Thani Province: A case study investigating farm size - Na nakorn, Amonpak; Chevakidagarn, Panalee; Danteravanich, Somtip (Agriculture and Natural Resources, 2017)
The environmental impact was studied due to water consumption and pollution loading from white shrimp culture at various shrimp farm scales. Field observation and in-depth interviews were carried out in 19 selected shrimp farms. The 38 water samples and 19 sediment samples from the shrimp farms from January-October, 2013 were analyzed and determined for their pollution loading from the wastewater and sediment discharged from the culture ponds. The results showed that for the same production, small-scale farms generated the highest pollution loading in wastewater and sediment, with respective values of per tonne production of 21.95 kg total Kjeldahl nitrogen and 1.12 kg total Kjeldahl nitrogen, 18.36 g Pb and 3.63 g Pb and 31.30 g As and 1.94 g As. However, for any-sized farm, the average total suspended solids and ammonia nitrogen of effluent from harvesting could not pass the Thai Effluent Standard for Coastal Aquaculture. In large-scale farms, the highest pollution loading per tonne production in wastewater discharged was 12.55 g Cu, while the highest pollution loadings per tonne production from the sediment generated were 20.98 kg organic matter, 0.079 g Cd and 26.65 g Cu. The large-scale farms used the highest proportion of refilled water (45.90%) and generated the highest amount of effluent during culture (39.26%). Only large-scale farms could manage their own control of water use to reduce environmental impacts. These results will be used further to determine the sustainability of shrimp farms at various scales.